(untitled) (DAPesquisa, 2020)
The complexity of emerging problems requires organizations to take a holistic view of the dimensions that surround them. Despite the disciplines, sustainable development, innovation and design management, dealing with complex and dynamic issues, their interactions are still unclear, even with common links. Thus, the objective of this paper is to understand the multidisciplinary relationship for sustainable social development between sustainable development, innovation and design management. To this end, exploratory research is carried out, of a qualitative nature and the use of bibliographic research as a method of data collection. The bibliographic research stage was carried out through a narrative literature review that involved the three disciplines to be addressed: sustainable development, innovation and design management. Based on this, the strategic articulation of design and innovation management around sustainable development was observed, in which innovation-oriented design management can creatively contribute to the resolution of real problems and generate disruptive changes in society, which allow us to conclude convergence between the disciplines treated.